Lay rationalities about madness and mental illness - Alves, Fátima (2020)
The way in wich societies relate to madness is in accordance with dominant concepts about the world (Benedict, 1934; Devereux, 1970). Modern racionality has created mental illness as an ‘object’ controled by medicine (Foucault, 1987).The concepts, attitudes and pratices associated with mental illness in modern societies are different in the scientific universe of psichiatry and in the lay universe that is culturally distant from the scientific representation of the body, the disease and the patient (Devereux, 1970). The semi-perifheric condition of Portuguese society is the factor which allows characteristics typical of developed societies to co-exist on a par with characteristics typical of less developed and less complex societies (Santos, 1990). This situation leads us to believe that inside the more universal system of modernity, the explanation of insanity and mentall illness in Portuguese society contains some specifics. The study that we present here centers on the lay knowledge system in explaining mental suffering and mental illness. In this context we try to understand to what level the common universe of perceptions, attitudes and practices associated with mental suffering and mental illness has been penetrated by psychiatry. What other thought and action systems apart from this, can people turn to? How people identifie, conceive, explain and deal with mental suffering and with mental illness? We try to understand the various elements of the mental life such as thoughts, beliefs, values, feelings, actions, as mediations of the interaction between the personal and the social and cultural spheres. This work was influenced by Geertz’s argument to describe experience from ‘the native’s point of view’ (Geertz, 1983) and the Lahire’s (2005) argument about the ‘plurality of habitus and contexts of action’ - deriving from Bourdieu’s (1979) conceptualisation about habitus - that influence the social action. Our report is the result of the analysis of information gathered from interviews with a diverse random sample of 68 men and women from the north of Portugal.